2003
DOI: 10.1088/0953-4075/36/5/325
|View full text |Cite
|
Sign up to set email alerts
|

Spin resonance with trapped ions

Abstract: A modified ion trap is described where experiments (in particular related to quantum information processing) that usually require optical radiation can be carried out using microwave or radio frequency electromagnetic fields. Instead of applying the usual methods for coherent manipulation of trapped ions, a string of ions in such a modified trap can be treated like a molecule in nuclear magnetic resonance experiments taking advantage of spin-spin coupling. The collection of trapped ions can be viewed as an N-q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(41 citation statements)
references
References 30 publications
0
41
0
Order By: Relevance
“…which is similar to M1K, appears in the most stabilizing quadruple mutation, M1R/E3K/K65I/E66L, found by the direct evolution method. [25] The quadruple mutation increases T m to above 858C, which is comparable with the midpoints of thermal denaturation of hyper-thermostable proteins. Unlike the mutation M1K, we were unable to find any experimental data about S11K or S11R.…”
Section: Full Papermentioning
confidence: 93%
See 4 more Smart Citations
“…which is similar to M1K, appears in the most stabilizing quadruple mutation, M1R/E3K/K65I/E66L, found by the direct evolution method. [25] The quadruple mutation increases T m to above 858C, which is comparable with the midpoints of thermal denaturation of hyper-thermostable proteins. Unlike the mutation M1K, we were unable to find any experimental data about S11K or S11R.…”
Section: Full Papermentioning
confidence: 93%
“…[16] While most of them reveal the key mutations leading to the improved thermostability of Bc-Csp, it is interesting that in a number of studies based on Proside method of direct evolution, the authors successfully found mutants that are quite different from the native thermophile, but have comparable, even improved thermostability with a melting temperature (T m ) up to 828C [24] and 858C. [25] Those temperatures are above the midpoint temperature of thermal unfolding of Bc-Csp (768C) and comparable to the midpoint of denaturation of the hyperthermostable analog from Thermotoga maritima.…”
Section: Combinatorial Scanning Mutagenesismentioning
confidence: 99%
See 3 more Smart Citations